Entrepreneurship : Riders Marketing / Nor Aini Hassanuddin ... [et al.] - Hassanuddin, Nor Aini; Ahmad, Nor Syahada; Ghazalli, Edatul Muliana; Abdul Ghani, Sawati; Ghazak, Julida (2002)
RIDERS MARKETING SDN. BHD. is a business that provides motorcycles only.The main reason of choosing this business because there are high demands for motorcycles. Many are more prefer to have motorcycle because the price is cheaper than other vehicles such as car and lorry. Besides, it is small and suitable for all. In other words, it is easy to handle.